Großräumige grenzüberschreitende Verflechtungsräume - Andrea Hartz; Gerd-Rainer Damm; Stefan Köhler (Raumforschung und Raumordnung, 2010)
A federal pilot project will explore the role played by economically strong border regions in interaction with European metropolitan and urban regions. Jointly with partners from the Maas-Rhine Euroregion, (SaarLorLux+) Euroregion, Trinational Upper Rhine metropolitan area and Lake Constance region, the regional policy of the federal government is aimed at establishing the particular importance of cross-border metropolitan areas for growth and innovation, as well as for the European target of territorial cohesion, within regional policy discussions in Germany and Europe. Testing the strategic approach of “supra-regional partnerships” in a cross-border context, is one significant aspect. The interests of the partners involved in the project are furthermore focussed on the regions themselves. This means, the project is dedicated to promote a coherent regional development, as well as effective cooperation structures across national borders. The project finally pursues the creation of an initiative in the form of an open alliance of cross-border metropolitan regions, in order to more effectively represent the interests of border regions on a national and European level. The article explores the genesis, objectives and approach of this pilot project against the background provided by current debates on sustainable spatial development in Germany and Europe.